2021
DOI: 10.1002/anie.202110441
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxy Radical‐Induced Formation of Dual‐Layered Protection Film for High‐Rate and Dendrite‐Free Lithium‐Metal Anodes

Abstract: The uncontrollable dendrite growth of Li metal anode leads to poor cycle stability and safety concerns, hindering its utilization in high energy density batteries. Herein, aphenoxy radical Spiro-O8 is proposed as an artificial protection film for Li metal anode owingt oi ts excellent filmforming capability and remarkable ionic conductivity.A spontaneous redoxr eaction between the Spiro-O8 and Li metal results in the formation of au niform and highly ionic conductive organic film in the bottom. Meanwhile,the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…1 However, many problems remain to be solved. 2,3 Increasing concerns for the environment, lack of lithium resources, and the use of toxic organic electrolytes have limited their further applications. 4,5 Compared with the lithium/sodium battery systems, rechargeable aqueous zinc ion batteries (AZIBs) have attracted extensive attention as a promising choice for largescale energy storage systems due to their excellent characteristics, 6 such as high theoretical specic capacity (820 mA h g À1 ), low redox potential (À0.76 V vs. SHE), reasonable price, and simplied assembly.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, many problems remain to be solved. 2,3 Increasing concerns for the environment, lack of lithium resources, and the use of toxic organic electrolytes have limited their further applications. 4,5 Compared with the lithium/sodium battery systems, rechargeable aqueous zinc ion batteries (AZIBs) have attracted extensive attention as a promising choice for largescale energy storage systems due to their excellent characteristics, 6 such as high theoretical specic capacity (820 mA h g À1 ), low redox potential (À0.76 V vs. SHE), reasonable price, and simplied assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the peak in the O 1s spectrum located at 528.3 eV (Figure b) may be associated with Li 2 O, which originates from the LiClO 4 additive that facilitates Li + transport and presents a more uniform electric field intensity distribution on the Li anode surface. , Furthermore, the existence of LiCl is further evidenced by the Li 1s spectrum in Figure c, the LiCl peak located around 56.3 eV, the Cl 2p spectrum in Figure d, the LiCl 2p 1/2 peak at 200.5 eV, and the LiCl 2p 3/2 peak at 198.9 eV. The F 1s spectrum in Figure S5 of the Supporting Information found that the LiF content on the surface of the negative electrode containing the most additive additions is relatively low, indicating that the additive addition can effectively reduce the decomposition of the electrolyte. More importantly, the electrochemical performance is effectively improved by benefiting from a stable and homogeneous SEI layer. The cycling CE in Li||Cu cells and cycle stability in complete cells are used to evaluate the reversibility of the Li metal anode in practical application, which is encouraged by the impressive interfacial strength in symmetric cells. The CEs of Li||Cu cells are shown in Figure a at current densities of 0.5 and 2 mA cm –2 , respectively, with a fixed deposition capacity of 1 mAh cm –2 .…”
Section: Resultsmentioning
confidence: 92%
“…The XPS spectra of graphite oxide and 1D-GNS show two major peaks at 282 and 534 eV for the C 1s and O 1s, respectively (Figure S2). Parts C and D of Figure compare the C 1s high-resolution XPS spectra of graphite oxide and 1D-GNS, in which the deconvoluted C 1s spectra of graphite oxide (Figure C) can be resolved into four components centered at 283.8, 285.5, 287.9, and 290.5 eV, representing C–C/CC, C–O–C/C–O, CO, and OC–O, respectively. In contrast, from the C 1s spectra of 1D-GNS (Figure D), the shrinking or even concealment of the peak area of the oxygen-containing groups can be seen, which can be attributed to the reduction of most of the oxygen-containing groups caused during the high-temperature treatment process in the Ar/H 2 atmosphere. Raman spectra can be used to judge the degree of disorder and graphitization, as shown in Figure E.…”
Section: Resultsmentioning
confidence: 99%